(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The conversation and modernization of the public sector is the ground of the good government and good governess. In our research, we examine a public service process of the Hungarian public sector. Our goal was to visualize the complex procedure as a whole (contact affair procedures in case of patchwork families) with Service Blueprinting and Business Process Modelling. After the process modelling, we used the discrete event simulation to analyze the elements of the process. Therefore, we are able to give a recommendation on how to improve the process for both the administrators and the legislators. With improving the effectiveness and efficiency, the government will be able to influence the satisfaction of customers and administrators. In the current procedure administrators are under the pressure, it is very stressful for them and the fluctuation is high in the office. We recommend for legislators to analyze the whole procedure in the public sector before the prescription of time limit. With the customer and administrator-oriented digitalization, the whole procedure can be more flexible and quicker. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.